Systemic antihyperalgesic effect of a novel conotoxin from Californiconus californicus in an inflammatory pain model - López-Carrillo, Joaquín; Bernáldez-Sarabia, Johanna; Pawar, Tushar J.; Jiménez, Samanta; Dueñas, Salvador; Figueroa-Montiel, Andrea; Olivares-Romero, José L.; Granados-Soto, Vinicio; Licea-Navarro, Alexei F.; Caram-Salas, Nadia L. (Frontiers in Pain Research, 2025)
IntroductionThis study explores the analgesic potential of the novel conotoxin O1_cal6.4b, derived from Californiconus californicus, as a candidate for pain management in a model of inflammatory pain.MethodsO1_cal6.4b was systemically administered to Wistar rats, and its effects on thermal hyperalgesia and motor coordination were evaluated. Comparative analyses were conducted against O1_cal6.4d, ω-MVIIA, and standard analgesics (morphine, dexamethasone, and diclofenac). Structural differences between O1_cal6.4b and O1_cal6.4d were examined using in silico modeling and molecular dynamics simulations.ResultsSystemic administration of O1_cal6.4b significantly reduced thermal hyperalgesia in a dose-dependent manner without impairing motor coordination. The analgesic effect of O1_cal6.4b was superior to that of O1_cal6.4d, ω-MVIIA, and standard analgesics. Structural analyses revealed notable differences between O1_cal6.4b and O1_cal6.4d, suggesting unique functional properties.DiscussionThe findings indicate that O1_cal6.4b exhibits a promising analgesic profile with advantages over traditional opioid-based therapies. These results underscore the molecular diversity of conotoxins and highlight their potential as innovative analgesic treatments. Further research is needed to elucidate the mechanism of action of this novel conotoxin.